Land-use modelling in planning practice - Koomen, Eric; Borsboom-van Beurden, Judith; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This book provides an overview of recent developments and applications of the Land Use Scanner model, which has been used in spatial planning for well over a decade. Internationally recognized as among the best of its kind, this versatile model can be applied at a national level for trend extrapolation, scenario studies and optimization, yet can also be employed in a smaller-scale regional context, as demonstrated by the assortment of regional case studies included in the book. Alongside these practical examples from the Netherlands, readers will find discussion of more theoretical aspects of land-use models as well as an assessment of various studies that aim to develop the Land-Use Scanner model further. Spanning the divide between the abstractions of land-use modelling and the imperatives of policy making, this is a cutting-edge account of the way in which the Land-Use Scanner approach is able to interrogate a spectrum of issues that range from climate change to transportation efficiency. Aimed at planners, researchers and policy makers who need to stay abreast of the latest advances in land-use modelling techniques in the context of planning practice, the book guides the reader through the applications supported by current instrumentation. It affords the opportunity for a wide readership to benefit from the extensive and acknowledged expertise of Dutch planners, who have originated a host of much-used models
PART I Introduction 1. Introducing the Land Use Scanner Koomen, Hilferink en Borsboom-van Beurden 2. Lumos-models from an international perspective Timmermans, Batty, Couclelis and Wegener 3. Core principles and concepts in land-use modelling: a literature review Van Schrojenstein Lantman, Verburg, Bregt and Geertman Part II Practice 4. A sustainable outlook on the future of The Netherlands Kuiper, Kuijpers-Linde, and Bouwman 5. Coupling detailed land-use model and a land-use and transport interaction model Zondag en Geurs 6. Biomass on peat soils Feasibility of bio energy production under a climate change scenario Kuhlman, Verburg, van Dijk and Phan-Drost 7. Simulation of future land-use for a developing regional spatial strategy The province of Overijssel Koekoek, Koomen, Loonen and Dijk 8. Lessons learned from using land-use simulation in regional planning Jacobs, Bouwman, Koomen and van der Burg Part III Future Developments 9. Explaining land-use transition in a segmented land market Potential input for Land Use Scanner Dekkers and Rietveld 10. A policy perspective of the development of Dutch land-use models Kuijpers-Linde 11 Developing a new market-based land use model Borsboom-van Beurden and Zondag
Includes bibliographical refences and index
Electronic reproduction
Keywords: Land use -- Mathematical models; Land use -- Planning